Primary Angiitis of the Central Nervous System - Mojdeh Ghabaee; Mohammad Hossein Harrirchian; Hossein Ali Ghelichnia Omrani; Hossein Pourmahmoodian; Babak Zamani; Majid Ghaffarpour (Acta Medica Iranica, 2012)
Primary angiitis of the central nervous system (PACNS) is an idiopathic disorder (vasculitis) restricted to the central nervous system (CNS). It often presents with focal neurological deficits suggesting stroke or a combination of confusion and headache. We herein report three cases with various combinations of fever, partial seizure, encephalopathy, paresis, headache and ataxia. One of them was initially treated as herpes simplex meningoencephalitis, but further investigations revealed primary angiitis. Primary angiitis of the CNS has protean manifestations and should always be considered in patients suspicious to have CNS infection or stroke, particularly who does not respond to the routine treatments. Clinical data, exclusion of differential diagnoses and typical angiography seem to be enough to justify the diagnosis in the majority of cases.